2008
DOI: 10.2174/1874241600801010047
|View full text |Cite
|
Sign up to set email alerts
|

Oxidant/Anti-Oxidant Status in Rats Exposed to Simulated Weightlessness by Hind-Limb Unloading and Reloading

Abstract: Hindlimb suspension or better known as hind-limb unloading (HLU) of rats is a validated model representing weightlessness, simulating microgravity. This is accomplished by removal of weight-bearing loads from hindquarters producing a cephalic fluid shift. The current study examines whether exposure to microgravity by hind-limb unloading will activate oxidant/antioxidant defense system. Tissue levels of malondialdehyde (MDA), total glutathione (GSH+GS-SG) and superoxide dismutase (SOD) were measured in harveste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 31 publications
1
17
0
Order By: Relevance
“…Also, it is known that SOD is a strong antioxidant that out-competes the reactions of O 2 . − to protect the cell from its toxicity [39]. The supplementation of 0.5% antioxidants (ARs or VE) with a high-fat diet did not significantly enhance SOD activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, it is known that SOD is a strong antioxidant that out-competes the reactions of O 2 . − to protect the cell from its toxicity [39]. The supplementation of 0.5% antioxidants (ARs or VE) with a high-fat diet did not significantly enhance SOD activity.…”
Section: Discussionmentioning
confidence: 99%
“…Although the mechanism of action requires further investigation, it would be presumed that ARs help increase GSH levels by direct reduction of GSSG through hydrogen atom transfer/donation or by free radical quenching, which indirectly helps maintain higher GSH levels. Since GSH has multiple roles in the endogenous antioxidant defense system, it is likely that GSH cooperates with SOD in the removal of free radicals [39]. This may explain the significant effects demonstrated by ARs on GSH, yet less pronounced or undetectable effects on SOD activity in the liver and heart, respectively, as ARs may only impact SOD activity indirectly through GSH.…”
Section: Discussionmentioning
confidence: 99%
“…Tail‐HLS was conducted as described previously (Chowdhury and Soulsby ; Chowdhury et al. ) using a tail harness constructed by looping a strip of Skin‐Trac orthopedic foam (Zimmer Inc., Charlotte, NC) around a pulley that can travel along a bar traversing the length of the cage.…”
Section: Methodsmentioning
confidence: 99%
“…The details of the method have been reported earlier from our laboratory (Chowdhury and Soulsby, 2008). We have earlier demonstrated that hind-limb unloaded rats maintained on a normal Purina diet displayed elevated stress as evidenced by elevated MDA levels in brain tissue harvested after two weeks of suspension (Chowdhury et al, 2007).…”
Section: Methodsmentioning
confidence: 99%
“…The pancreata were extracted for measurements of malondialdehyde (MDA) and glutathione levels. Our preliminary studies (Chowdhury et al, 2007 andSoulsby, 2008) have demonstrated that HLS rats maintained on a normal Purina diet, displayed elevated malondialdehyde (MDA) and glutathione levels.…”
Section: Methodsmentioning
confidence: 99%